Molecular Changes in White Matter Adjacent to an Active Demyelinating Lesion in Early Multiple Sclerosis - Zeis, Thomas (Brain Pathol, 2008)
A stereotactic biopsy of a 17‐year‐old woman revealed an active inflammatory demyelinating lesion compatible with pattern III multiple sclerosis (MS) according to Lucchinetti et al. The biopsy included a white matter region distant from the active inflammatory demyelinating lesion with abnormal MRI signal, lacking histopathological signs of demyelination and/or oligodendrocyte apoptosis. Expression analysis of this area revealed a strong up‐regulation of neuronal nitric oxide synthase (nNOS). Furthermore, detection of nitrotyrosine provided evidence for reactive nitrogen species (RNS)‐mediated damage to oligodendrocytes. Concomitantly, genes involved in neuroprotection against oxidative stress such as heme oxygenase 1 were up‐regulated. Even though a single case report, this study shows earliest molecular changes in white matter surrounding an actively demyelinating lesion during the first manifestation of MS, pointing toward a more widespread pathological process. Therapeutic targeting of the identified mechanisms of tissue injury might be crucial to prevent further lesion formation or secondary tissue damage.